Evaluation of teaching factory in collaboration with PT. Telkom for the adaptability development of vocational school students ICT expertise program using CIPP - Sunaryo, Ari; Widiyanti, Widiyanti; Nurjannah, Nunung (Technium Social Sciences Journal, 2021)
This study aims to combine business ideas with vocational or vocational education that is commensurate with the competence of ICT expertise, the process of implementing the Teaching Fac—teaching). Teaching Factory (TEFA) which is implemented using the concept of Context, Input, Process, and Product. The approach used in this research is qualitative which is supported by quantitative data by solving case studies. The results of the research in the evaluation of the Teaching Factory (TEFA) showed that the implementation of the Teaching Factory at SMKN 1 Boyolangu Tulungagung using the CIPP model resulted in 89% being very in line with the criteria, but the thing to note from this assessment is that adjustments are needed to the main teacher competencies in the implementation of Teaching Factory. (TEFA).